Implementation of a nurse-led, multidisciplinary model of care for older adults with cancer: a process evaluation protocol - Sagun Parakh; Kathryn Lee; Jeremy Rodrigues; Paul Yates; Polly Hypatia Dufton; Elena Tarasenko; Katrina Midgley; Ray Kelly; Surein Arulananda (BMJ Open)
Introduction Cancer is predominantly a disease of older adults, with an increasing number of cancer diagnoses in individuals aged 65 or older. Multiple geriatric factors have been shown to impact patient outcomes in cancer treatment. However, oncology specialists are not well adapted to incorporate geriatric assessment into practice due to a lack of resources and knowledge of the specialty.The primary aim of this study is to implement and evaluate a nurse-led, multidisciplinary model of care for older adults with cancer at two public tertiary hospitals in Melbourne, Australia.Methods and analysis This study will aim to assess 200 patients across 2 sites. Both sites will assess individuals with lung cancer; the second site will also include individuals with genitourinary, upper gastrointestinal and colorectal cancers.This process evaluation will use quantitative and qualitative methods to explore the reach, effectiveness, adoption, implementation, and maintenance (RE-AIM) of the nurse-led, multidisciplinary model of care.Ethics and dissemination Ethical approval and local governance approvals have been obtained by Austin Health and Monash Health Human Research Ethics committees. Dissemination will occur via publications, conferences, social medical and local engagement with clinicians, consumers and managers.